PERBEDAAN HASIL BELAJAR FISIKA SISWA KELAS X SMA NEGERI 3 TERNATE DENGAN MENGGUNAKAN PEMBELAJARAN INQUIRY TERBIMBING DAN PEMBELAJARAN KONVENSIONAL PADA MATERI LISTRIK DINAMIS - Hasan, Siti Nahria; Sehat, Suleman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This study aims to determine differences in the results of learning physics class X SMA 3 Ternate using guided inquiry learning and conventional learning in dynamic electrical material This research is a quasi experimental . The population in this study were all students of class X SMA 3 Ternate second half totaling 196 people. Sampling was done by random sampling by taking two classes were randomly ie class as a class X - 1 and X - 2 experiment as a control class , each class numbered 34 students. The instrument used to know the test results of student learning is the learning outcomes in the form of multiple choice with a number of 30 items . The results obtained by the average value of each class X - 1 and X - 2 was 72.88 and 54.79 . There are differences in student learning outcomes using guided inquiry learning and conventional learning . This is seen in testing the hypothesis that the results obtained = 3.09 and = 2.00. > or 3.09 > 2.00. Keywords: Inquiry Terbimbing, Pembelajaran Konvensional, Hasil Belajar.